Conservative surgery of the mitral valve in bacterial endocarditis. Issue 11 (November 1984) - Gammage, M D; Littler, W A; Abrams, L D
Abstract : Surgical repair of the mitral valve was undertaken in two young female patients during the active phase of bacterial endocarditis to eradicate persistent infection. Operation resulted in rapid resolution of infection with good haemodynamic results in both patients. A mitral valve prosthesis has the disadvantage for children of needing replacement because of growth, and for young women of leading to problems in pregnancy because of the need for lifelong anticoagulant treatment. Thus repair rather than replacement of the mitral valve should be considered in patients, especially young women, presenting with mitral regurgitation in these circumstances.